Solutions and the Generalized Hyers-Ulam-Rassias Stability of a Generalized Quadratic-Additive Functional Equation - M. Janfada; R. Shourvazi (Abstract and Applied Analysis)
We study general solutions and generalized Hyers-Ulam-Rassias stability of the following 𝑛-dimensional functional equation ∑𝑓(𝑘𝑖=1𝑥𝑖∑)+(𝑘−2)𝑘𝑖=1𝑓(𝑥𝑖∑)=𝑘𝑖=1∑𝑘𝑗=1,𝑗>𝑖𝑓(𝑥𝑖+𝑥𝑗), 𝑘≥3, on non-Archimedean normed spaces.